Education Policy of Sudan and Utilization of the Mobile Device (iPad) Technology: Opportunities and Challenges - Saifaldin Idris Onia (Indonesian Journal of Educational Research and Technology, 2022)
The Sudanese education system, in recent years, has seen a significant expansion because of the significant increase in the numbers wishing to learn. There is a necessary need for expanding educational services to cover this vast number of scholars. The existing service is showing a clear deficit through physical, human, and spatial limitations. This illustrates the necessity to employ modern technologies such as mobile devices (iPad) to support education. Therefore, this paper seeks to review the use of mobile device (iPad) technology in education and explore the opportunities and challenges of utilizing iPad technology in the education system of Sudan. This paper reached to the use of mobile device (iPad) technology in the Sudanese education system providing opportunities for networking learning, social learning, interactive learning, and distance learning.  There are several challenges facing the utilization of mobile device (iPad) technology in the Sudanese education system in which the delivery of information by traditional methods is better than the use of mobile learning, there is no clear plan for the usage of mobile devices by the competent authorities, lack of training to use and employ the mobile learning. The paper recommended providing facilities to improve opportunities to incorporate technology into the Sudanese education system.